Rancang Bangun Sistem Informasi Monitoring dan Evaluasi Pelaksanaan Program Tuberkulosis Berbasis Web - Rizal Pratama Suganda; Sulistiowati Sulistiowati; Yoppy Mirza Maulana (Jurnal Sistem Informasi Universitas Dinamika, 2016)
Dinas Kesehatan (Dinkes) Kota Surabaya is a Surabaya Government institution who has responsibility in medical of Surabaya people. Dinkes kota Surabaya has a section in controling and eradicating of communicable desease where its role is preventing and overcoming city communicable desease. And the one of communicable desease is Tuberculosis. Tuberculosis is a communicable desease was caused by microbacterium tuberculosa where it was more infected the lungs than any organs of the body. On the progress of controling tuberculosis, Dinkes Kota Surabaya had the problem in monitoring and eveluation proses where it was caused by the presentation form today still unrealtime than it takes a lot of time to find out the changing.Based on the problem was said, it was known that Dinkes Kota Surabaya need information system which can be monitoring and evaluating realtime.And based on the test result and evaluation, information system that was created can be monitoring and evaluating realtime, then Dinkes kota Surabaya can act quickly if it got puskesmas in minimum line indikator.